To what extent can drama in education pedagogy improve the learning experiences of international students in Higher Education - Ji, Lin (Trinity College (Dublin, Ireland). School of Education, 2021)
This study explores whether and to what extent drama in education (DiE) can improve international student learning experience in Higher Education, in particular using DiE pedagogy to enhance their group collaboration and cooperation, social and communication skills. This dissertation is presented in seven chapters. Chapter 1 introduces the context of the work. Chapter 2 and 3 are the literature reviews, which outline the international students current learning status’ and suggests that learning through drama can encourage students to collaborate more, interact and communicate better in a social context. Chapter 4 sets out research approaches which informed the data collecting and analysis. Findings and discussion are displayed in chapters 5 and 6 respectively. Chapter 7 provides a conclusion and recommendations. The research was implemented in Trinity College Dublin, on the 30th May and the 4th June 2019, and consisted of two 2.5-hour lessons. Thirteen participants attended the drama lessons, while team-teaching and researcher’s reflective observations took place during this time. Participants were invited to complete semi-structured interviews before and after the intervention, which were used for analysing the change in the students’ opinion of their learning experiences. This study found: • DiE enabled students to develop their emotion and cognition in an interactive learning. • DiE enriched students’ interaction in group participation and enhanced their learning empowerment. • DiE improved students’ social and communication skills, particularly their problem-solving and creativity skills in the fictitious situations. The study recommends using DiE pedagogy to develop international student engagement, through different drama techniques to foster their social and communication skills, while learning to work cooperatively.
Keywords: Drama in Education; Education